Shortening gestational age at term and organisation of birth care in the Czech Republic - Štípková, Martina (The International journal of health planning and management, 2018)
A trend of the shortening duration of pregnancies carried to term has been observed in several countries and represents a growing public health concern. This paper describes the trend in the Czech Republic and shows its relation to the changing demographic structure of mothers and the organisation of maternity care. Data from the birth register are used and supplemented with information about the capacity of maternity care (number of beds at maternity clinics, number of obstetricians and midwives). Logistic regression is used to estimate the odds of 37 to 39 vs 40+ completed weeks of gestation. The results show that the average gestational age at term decreased by 2.1 days between 2000 and 2013. The odds of 37 to 39 weeks of gestational duration increased, mainly due to the reduction in the number of beds at maternity clinics (adjusted odds ratio of 1.51). The effects of the number of health care staff members were weaker. The number of midwives positively influenced gestational duration, while the number of obstetricians had a negative effect. Maternal demographic structure cannot explain the trend. A likely explanation is the increased use of planned early term caesarean sections.
Keywords: Registries; logistické modely; Humans; Hospital Bed Capacity; registrace; hodnocení výsledků zdravotní péče; Midwifery; gestační stáří; Female; mladý dospělý; dospělí; babictví; lidé; lůžková kapacita nemocnice; indukovaný porod; Adult; Term Birth; ženské pohlaví; Maternal Health Services; porod v termínu; Czech Republic; služby zdravotní péče o matku; Young Adult; Česká republika; Outcome Assessment, Health Care; Logistic Models; Gestational Age; Labor, Induced